Economic assessment of molecular imaging in the oncology treatment process - Schnitzer, Moritz Ludwig; Kremer, Christophe; Hertel, Alexander; Haselmann, Verena; Münchhausen, Niklas, Freiherr von; Schönberg, Stefan; Froelich, Matthias F. (European journal of radiology, 2022)
The development towards targeted treatments in oncology has been accompanied by significant improvements in molecular imaging. Yet, broad application of novel imaging techniques has partly been slowed down due to economical considerations. Building on the broad positive evidence of its diagnostic accuracy, modelling of effects on long-term costs and effectiveness may help to foster a broader application and acceptance of comprehensive molecular imaging techniques, such as PET/MRI. In this article, common economic evaluation techniques and cost-effectiveness analysis (CEA) evaluation methods will be introduced including Markov models and incremental cost-effectiveness ratios (ICER). This is complemented with a review of literature on recently published cost-effectiveness of molecular imaging. Additionally, the strategic relevance of CEAs for the molecular imaging community is discussed and combined with a global outlook.
Available online 13 December 2021
Gesehen am 22.06.2023